Determinantes envolvidos na resposta imune celular humana à infecção por Leishmania infantum chagasi - Lacerda, Hênio Godeiro (2011)
Visceral leishmaniasis (VL) is a disease caused by protozoa of the Leishmania donovani complex, whose infection has clinical spectrum ranging from asymptomatic infection to active disease characterized by fever, cachexia, hepatosplenomegaly, and immunosuppression. The healing or protective immunity require an antigen-specific type 1. The Montenegro skin test (DTH) has been interpreted as a marker of protective immunity. However, there is no known correlation between the DTH response to type 1 and DTH and immunity of type 1 are maintained in the long term. Thus, a longitudinal study of 8 years, nested in a cohort family held in Brazil, documented the status of DTH and cytokine production by peripheral blood mononuclear cells in response to antigen-specific stimulation. This study was the interdisciplinary approach of physicians, biochemists, nutritionists, veterinary medicine, biology and statistics. The results show that 46.2% of subjects were analyzed DTH positive at baseline. The prevalence of positive and DTH induration size increased with age (p = 0.0021). 15.7% of individuals positive DTH "retro-converted" the negative and 50.4% (64) of individuals negative DTH became positive. The size of DTH induration was correlated significantly with the antigen-induced production of IFN-γ (r = 0.6186, p = 0.0001). IL-6 was secreted at higher levels in peripheral blood mononuclear cells of individuals who "retro-converted" DTH positive to negative than individuals who remained stable DTH status (p = 0.005). Thus, IFN-γ produced by peripheral blood mononuclear cells, may be a surrogate marker for protective immunity instead of the DTH response. In addition, differences in innate immune response may determine whether individuals maintain or eliminate the infection by Leishmania infantum chagasi in asymptomatic patients